Tomato SlAN11 regulates flavonoid biosynthesis and seed dormancy by interaction with bHLH proteins but not with MYB proteins - Yongfeng Gao; Jikai Liu; Yongfu Chen; Hai Tang; Yang Wang; Yongmei He; Yongbin Ou; Xiaochun Sun; Songhu Wang; Yinan Yao (Horticulture Research, 2018)
Tomatoes: a protein control for flavonoids Insights into the production of important nutrients called flavonoids are revealed by a molecular and genetic study of tomatoes. Flavonoids are a diverse group of chemicals with a variety of metabolic functions, and which contribute to the characteristic colors of many fruits and vegetables. They have been linked with health benefits due to their antioxidant, anti-inflammatory, and immune-regulating activities. Researchers in China, led by Yinan Yao at Southwest University of Science and Technology, explored the activity of a protein known as  SlAN11. They found that the protein interacts with other proteins to regulate the activity of specific genes, increasing the production of flavonoids called anthocyanins. SlAN11 also regulates the dormancy process in tomato seeds. Geneticists may use the results to generate new breeds of tomato plants enriched in flavonoids to promote good health.